Uterine fibroid embolization in Poland – where are we after 10 years? - Pietura, Radosław (Menopause Review/Przegląd Menopauzalny, 2011)
Within the last decade the spectrum of treatment of uterine leiomyoma has broaden with methods causing ischemia of fibroids. Arterial embolization is a long established technique in the treatment of abdominal and pelvic haemorrhage but has only recently been used to treat uterine leiomyoma. Uterine fibroid embolization was developed by Ravina in Paris in 1994. At the beginning he use embolization as a preoperative procedure. First paper regarding uterine fibroid embolization was published in 1995. In Poland first embolization for uterine fibroids was performed in 2001. Nowadays standards for radiologist training, technical aspects of procedure, postprocedural patient care, long-term results are well established and recommended by Society of Interventional Radiology and Cardiovascular and Interventional Radiology Society of Europe. Paper presents analysis of literature, author clinical experience and medical societies recommendations. This review is focused not only on embolization long-term results and complications but mostly on role of embolization in uterine fibroid managements.